C.R.A.B.: a gamified paradigm for studying readiness potential - Blagovechtchenski, Evgeny; Koriakina, Maria; Bartseva, Ksenia; Kuznetsova, Alexandra; Kirsanov, Aleksandr; Ponomareva, Sofia; Popyvanova, Alena; Pomelova, Ekaterina (Frontiers in Human Neuroscience, 2025)
BackgroundThis study presents a novel paradigm termed Contrasting Routines Affecting Bereitschaftspotential (C.R.A.B.), designed to analyze readiness potential (RP) waveforms preceding movements across varying experimental settings. This paradigm continues Libet's work on decision-making, with an emphasis on the motor planning component like in classical Libet experiment. However, existing paradigms for studying RP work poorly across ages (requiring different instructions) and do not accurately identify the components associated with RP formation.New methodThe C.R.A.B. paradigm enables modeling the when-decision through indirect measurements, thereby avoiding reliance on participants' introspective reports. We believe that this framework can isolate the motor planning component from decision-making and is also suitable for implementation with children of different ages and disorders.ResultsAs a proof of concept, we employed the C.R.A.B. paradigm with healthy adult participants to validate its effectiveness. Our findings revealed distinct RP waveform variations across different trial conditions. Comparison with existing methods C.R.A.B. paradigm has several advantages over traditional methods: the design of the experiment provides for the assessment of different components of RP—motor planning, attention level, and spontaneity of decision-making since the design of the experiment is developed in a game form, it is suitable for both children and adults.ConclusionsThe C.R.A.B. paradigm effectively demonstrated differences in RP waveforms across trial types; therefore, this paradigm can be used to study the various components of the RP in detail. Since this paradigm represents a game interface, it is possible to study the RP in children, including children with various disorders.